2016
DOI: 10.1038/icb.2016.100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth hormone and IgG aggregates on dendritic cells activation and T‐cells polarization

Abstract: Patients treated with therapeutic biological products (BP) frequently develop anti-drug antibodies (ADA) with potential neutralizing capacities leading to loss of clinical response or serious side effects. BP aggregates have been suggested to promote immunogenicity, thus enhancing ADA production. Dendritic cells (DC) are key effectors in T-cell and B-cell fates, and the subsequent generation of immunogenicity. The objective of this work was to determine if BP aggregates can participate to DC maturation and T-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 45 publications
3
38
0
Order By: Relevance
“…Several studies have shown that under accelerated stress conditions, proteins can give mixtures of soluble aggregates that are submicron species including oligomers or multimers, mostly detected with dynamic light scattering method, and insoluble aggregates that are above the micrometer range (37). This was the case for human growth hormone submitted to a stir stress that gave homogenous aggregates around 892 nm (38), or antibody preparations that underwent stir stress (39), or thermal stress (40, 41). Another study showed the appearance of nanosized antibody aggregates upon heat or pH-shift stress that persisted when preparations were diluted in human serum, highlighting the interactions of aggregated proteins with biological fluids (42).…”
Section: Protein Aggregates As Nps Can Drive Immune Responsesmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have shown that under accelerated stress conditions, proteins can give mixtures of soluble aggregates that are submicron species including oligomers or multimers, mostly detected with dynamic light scattering method, and insoluble aggregates that are above the micrometer range (37). This was the case for human growth hormone submitted to a stir stress that gave homogenous aggregates around 892 nm (38), or antibody preparations that underwent stir stress (39), or thermal stress (40, 41). Another study showed the appearance of nanosized antibody aggregates upon heat or pH-shift stress that persisted when preparations were diluted in human serum, highlighting the interactions of aggregated proteins with biological fluids (42).…”
Section: Protein Aggregates As Nps Can Drive Immune Responsesmentioning
confidence: 99%
“…As therapeutic proteins can be processed by DCs to be presented to T cells, aggregates can interact with pattern recognition receptors, and then induce DCs activation. Indeed, several studies have shown that antibodies or growth hormone (GH) aggregates have the capacity to induce monocyte-derived dendritic cells maturation, evidenced by an increase in phenotypic markers expression, as well as cytokine or chemokine production (38, 57, 58). Both GH and antibodies aggregates could induce the production of IL-6, IL-8, IL-12p40, and CXCL10 whereas CCL2, CCL3, CCL4 production was only seen with GH aggregates (38).…”
Section: Protein Aggregates As Nps Can Drive Immune Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…3 We, and others, have previously shown that protein aggregates could act as a danger signal and be recognized by dendritic cells inducing their maturation and CD4 þ T-cell response. 5,6 In a previous work, we demonstrated that human growth hormone (hGH) aggregates were able to induce monocytederived DC (moDC) maturation, showed by a significant increase of surface markers expression and a high production of proinflammatory cytokines and inflammatory chemokines with notably an increase in CXCL10 secretion compared to the native protein.…”
Section: Introductionmentioning
confidence: 99%